Cardiac biomarkers predict mortality in emergency patients presenting with atrial fibrillation. Issue 6 (10th November 2018) - Niederdöckl, Jan; Simon, Alexander; Schnaubelt, Sebastian; Schuetz, Nikola; Laggner, Roberta; Sulzgruber, Patrick; Spiel, Alexander O; Herkner, Harald; Laggner, Anton N; Domanovits, Hans
Abstract : Objectives: To assess the predictive value of N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitive troponin T (hs-TnT) serum levels for mid-term mortality in patients presenting with symptomatic atrial fibrillation (AF) to an emergency department. Methods: Non-interventional cohort/follow-up study, including consecutive patients presenting to a tertiary care university emergency department due to symptomatic AF between 2012 and 2016. Multivariable Cox proportional hazard regression models were used to estimate the mortality rates and hazards per 100 patient-years (pry) for NT-proBNP and hs-TnT serum levels in quintiles. Results: 2574 episodes of 1754 patients (age 68 (IQR 58–75) years, female gender 1199 (44%), CHA2 DS2 -VASc 3 (IQR 1–4)) were recorded. Following the exclusion of incomplete datasets, 1780 episodes were available for analysis. 162 patients deceased during the mid-term follow-up (median 23 (IQR 4–38) months); the mortality rate was 4.72/100 pry. Hazard for death increased with every quintile of NT-proBNP by 1.53 (HR; 95% CI 1.27 to 1.83; p<0.001) and by 1.31 (HR; 95% CI 1.10 to 1.55; p=0.002) with every quintile of hs-TnT in multivariate Cox-regression analysis. No interaction between NT-proBNP and hs-TnT levels could be observed. Conclusion: Elevated NT-proBNP and hs-TnT levels are independently associated with increased mid-term mortality in patients presenting to an emergency department due to symptomatic AF. Trial registration number: NCT03272620 ; Results.